INFORMATION MEDIA PUBLIC SERVICE ADVERTISEMENT ABOUT VCT BASED ON 2D ANIMATION - Trisemarawima, I Nyoman Yoga; Prayoga, I Kadek Martha; Jayanegara, I Nyoman; Yasa, I Wayan Adi Putra (Journal of Aesthetics, Design, and Art Management, 2024)
Purpose: to design information media for public service advertisements about the importance of 2D animation-based VCT tests. Research methods: the research was conducted qualitatively by collecting data through interviews, observation, literature and documentation. The design process is carried out through three stages, namely pre-production, production and post-production. Findings: The design of public service advertisement information media is carried out through three stages. First, the pre-production process by designing simple design concepts, visual elements to storyboards and scenarios. The second stage enters the production process by realizing and combining all visual assets in the software. The third stage is post-production, which is the rendering process to produce a public service advertisement video that is ready to be distributed to the public. Implications: 2D animation-based public service advertisement media is communicative, informative and easy to understand and is suitable for display in the community.